Access to Nature via Virtual Reality: A Mini-Review - Li, Hansen; Zhang, Xing; Wang, Hongying; Yang, Zongqian; Liu, Haowei; Cao, Yang; Zhang, Guodong (Frontiers in Psychology, 2021)
Nature exposure is known to promote physical and mental health. However, an actual nature exposure may not be easily achieved for the population with physical disabilities or chronic conditions. Therefore, many attempts have been made to duplicate nature exposure via media devices, and virtual reality (VR) is deemed as a promising technology due to its advantage in creating a sense of immersion. Generally, the current studies suggest that being exposed to virtual nature may contribute to psychological and physiological relaxation. Besides, some evidence indicates that virtual nature may promote attentional resources, cognitive performance, and pain experience. Though VR is deemed as an advanced media, insufficient evidence was found concerning the advantages of VR over traditional 2D media for the simulated nature exposure. On the other hand, computer-generated (CG) scenarios were found might be more beneficial than 360-video, and mini-games may be useful to create an interactive VR format for simulated nature exposure. Further research is warranted because of the limited relevant studies.